2021
DOI: 10.1016/j.neubiorev.2019.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Still no evidence that exergames improve cognitive ability: A commentary on Stanmore et al. (2017)

Abstract: A recent meta-analysis (Stanmore et al. Neurosci. Biobehav. Rev. 78:34-43, 2017) claimed that exergames exert medium-size positive effects on people's overall cognitive function. The present article critically tests this claim. We argue that the meta-analysis reported inflated effect sizes mainly for three reasons: (a) some effect sizes were miscalculated; (b) there was an excessive amount of true heterogeneity; and (c) no publication-bias-corrected estimates were provided. We have thus recalculated the effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…For instance, WM training does not enhance children's domain-general cognitive skills or academic achievement (Aksayli, Sala, & Gobet, 2019;Melby-Lervåg et al, 2016;Sala & Gobet, 2020). The same applies to action and nonaction videogame training and brain training (Duyck & Op de Beeck, 2019;Kassai, Futo, Demetrovics, & Takacs, 2019;Libertus et al, 2017;Lintern & Boot, 2019;Sala et al, 2019a;Sala, Tatlidil, & Gobet, 2018, 2019bSimons et al, 2016).…”
Section: Beyond Meta-analytic Evidencementioning
confidence: 99%
“…For instance, WM training does not enhance children's domain-general cognitive skills or academic achievement (Aksayli, Sala, & Gobet, 2019;Melby-Lervåg et al, 2016;Sala & Gobet, 2020). The same applies to action and nonaction videogame training and brain training (Duyck & Op de Beeck, 2019;Kassai, Futo, Demetrovics, & Takacs, 2019;Libertus et al, 2017;Lintern & Boot, 2019;Sala et al, 2019a;Sala, Tatlidil, & Gobet, 2018, 2019bSimons et al, 2016).…”
Section: Beyond Meta-analytic Evidencementioning
confidence: 99%
“…(Anderson-Hanley et al, 2012;Maillot et al, 2012;Barcelos et al, 2015;Eggenberger et al, 2015;Schättin et al, 2016;Ballesteros et al, 2018)], controversial findings have also been reported as exergames were found to be effective [e.g. (Stanmore et al, 2017)], ineffective (Ordnung et al, 2017;Sala et al, 2019), or unclear (Stojan and Voelcker-Rehage, 2019), in comparison with conventional interventions. Several reasons may explain these inconsistencies.…”
Section: Are Exergames Effective For Enhancing Brain Plasticity and Cognition?mentioning
confidence: 99%
“…Although exergames do not appear to outperform conventional physical training in terms of cognitive effects [30], they may be a motivating vector to promote adherence to physical exercise. Recent meta-analyses and systematic reviews indicated that playing exergames can benefit executive function, attention and visuospatial processing in HOA and MCI [30,31], although the results of the former have been challenged [32]. In an RCT in 78 individuals with MCI, playing sports video games on the Nintendo Wii for 30 min three times a week over 10 weeks yielded more significant effects in the digit span (working memory) and also health-related quality of life than the same dose of the CoTras CCT program [33 & ].…”
Section: Exergamesmentioning
confidence: 99%